Pengaruh Kompetensi, Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Ciamis - Ading Rahman Sukmara; Fajar Yudistira; Irma Bastaman (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The purpose of this study was to determine the Influence of Competence, Motivation and Work Discipline on the Performance of Employees of the Investment and One-Stop Integrated Service Office of Ciamis Regency. In this study, the author used a quantitative research method, including subject selection, data collection techniques (such as questionnaires, observation and interviews). With the measurement scale used in this study is Likert. With the sampling technique using the total sampling technique, namely all employees of the Investment and One-Stop Integrated Service Office of Ciamis Regency in 2019 as many as 44 people. The results of the study showed that 1). There is an influence of competence on employee performance, the correlation coefficient value (R) of 0.767 means that the better the employee's competence, the employee's performance will increase, 2). There is an influence of motivation on employee performance, the correlation coefficient value (R) of 0.633 means that the better the motivation, the employee's performance will increase, 3). There is an influence of work discipline on employee performance, the correlation coefficient value (R) of 0.672 means that the better the work discipline, the employee's performance will increase, 4). There is an Influence of Competence, Motivation and Work Discipline on Employee Performance, the correlation coefficient value (R) is 0.839, meaning that the better the Competence, Motivation and Work Discipline, the more effective the employee performance will be. Based on the calculation, it is known that F count 31.785> F table 3.23, so the relationship between X1, X2, X3 and Y is significant. In other words, the hypothesis proposed by the author can be accepted because it has been statistically tested.